PRAGMATIC AND DISCURSIVE FEATURES OF EMOTIONAL EXPRESSION IN ALEXANDER FAYNBERG’S POETRY - Abdumalikova Sevinch Tayirovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article investigates the pragmatic and discursive dimensions of emotional expression within the poetic corpus of Alexander Faynberg. Beyond simple thematic  analysis,  the  study  explores  how  Faynberg  utilizes  linguistic  strategies  to perform emotions and engage the reader in a shared psychological space. By examining speech acts, deictic markers, and modal structures, the research identifies how the poet constructs "emotive discourse." The analysis focuses on the pragmatics of sincerity, the  discursive  representation  of  nostalgia,  and  the  use  of  silence  as  an  emotional signifier. The findings suggest that Faynberg’s poetry operates as a communicative event  where  emotions  are  not  merely  described  but  are  linguistically  enacted  to influence the reader's affective state. This approach provides a deeper understanding of the functional aspects of his style and his ability to bridge the gap between individual experience and collective discourse.